Let Me Admit Impediments - Sophie Van Laak, Felicitas (Satura, 2022)
The turn-taking touch of sunlight and shade As I walk beneath these lovers’ eyes, Writing stories on my skin. Shy crowns are devoid of coronation. Reaching for each other’s hands, tenderly. Almost tangible, never touching.